2020
DOI: 10.1101/2020.09.01.277780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling SARS-CoV-2 infectionin vitrowith a human intestine-on-chip device

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2) has given rise to a global pandemic. The gastrointestinal symptoms of some COVID-19 patients are underestimated. There is an urgent need to develop physiologically relevant model that can accurately reflect human response to viral infection. Here, we report the creation of a biomimetic human intestine infection model on a chip system that allows to recapitulate the intestinal injury and immune response indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Notably, they showed distinct responses of two cell types to SARS-CoV-2 infection, including activation of the type I interferon signaling cascade in epithelium and the Janus kinase-signal transducer and activator of transcription ( JAK-STAT) signaling pathway in the endothelium. Guo et al(65) created a microengineered intestineon-a-chip device to mirror the pathophysiological features and immune responses in COVID-19. This model contains cocultured human intestinal epithelial (Caco-2) cells and mucin-secreting HT-29 cells lined in the upper channel and human umbilical vein endothelial cells in the lower channel under fluidic conditions.…”
mentioning
confidence: 99%
“…Notably, they showed distinct responses of two cell types to SARS-CoV-2 infection, including activation of the type I interferon signaling cascade in epithelium and the Janus kinase-signal transducer and activator of transcription ( JAK-STAT) signaling pathway in the endothelium. Guo et al(65) created a microengineered intestineon-a-chip device to mirror the pathophysiological features and immune responses in COVID-19. This model contains cocultured human intestinal epithelial (Caco-2) cells and mucin-secreting HT-29 cells lined in the upper channel and human umbilical vein endothelial cells in the lower channel under fluidic conditions.…”
mentioning
confidence: 99%
“…Also, microfluidic-based 3D models and organ-on-a-chip systems provide biomimetic environment with air and fluid flows typical of what normally occurs in the lung, and can be useful for studying viral infection [29]. Therefore, the development of OoC-based technology to study the response of human tissues and organs to SARS-CoV-2 is urgently needed [98].…”
Section: Organ-on-a-chip Systemsmentioning
confidence: 99%
“…For example, gut-on-a-chip systems represent an attractive tool to study health and disease states [99], and they can be used to study SARS-CoV-2 infection. Recently, Guo et al [98] reported the development of a SARS-CoV-2 infection in vitro using a biomimetic human intestine-on-a-chip device for studying of COVID-19. The intestine-on-a-chip device contained two parallel, cell culture microchannels, an upper epithelial cell-lined channel (co-cultured human intestinal epithelial cells and mucin secreting cells) and a lower vascular endothelial cell-lined channel separated by a thin flexible polydimethylsiloxane (PDMS) membrane which was coated with ECM.…”
Section: Organ-on-a-chip Systemsmentioning
confidence: 99%
“…To study recapitulated alveolar-capillary barrier injury and inflammatory responses of SARS-CoV-2 infection, Zhang and his co-worker created a micro-engineered alveolus chip model [54]. Similarly, to recapitulate the intestinal injury and immune response by SARS-CoV-2, Yaqiong Guo and colleagues engineered an intestine-on-chip device [55]. Besides, the microfluidic model of the human blood-brain barrier indicated that spike protein subunits of SARS-CoV-2 can affect the function of blood-brain barrier [56].…”
Section: Organ-on-chipmentioning
confidence: 99%